Rare Disasters, Asset Prices, and Welfare Costs - Barro, Robert J (American Economic Review, 2009)
A representative-consumer model with Epstein-Zin-Weil preferences and i.i.d. shocks, including rare disasters, accords with observed equity premia and risk-free rates if the coefficient of relative risk aversion equals 3–4. If the intertemporal elasticity of substitution exceeds one, an increase in uncertainty lowers the price-dividend ratio for equity, and a rise in the expected growth rate raises this ratio. Calibrations indicate that society would willingly reduce GDP by around 20 percent each year to eliminate rare disasters. The welfare cost from usual economic fluctuations is much smaller, though still important, corresponding to lowering GDP by about 1.5 percent each year. (JEL E13, E21, E22, E32)